Cell-free layer (CFL) analysis in a glass capillary: comparison between a manual and automatic method - Bento, David (2014)
In this study, in vitro blood flowing through a 100 m glass capillary was studied. The images were captured using a confocal system and post-processed using Image J and MatLab. The aim of the present work, was to measure the trajectories of the cell-free layer (CFL) by using two different methods, i. e., a manual method (MM) and an automatic method (AM). For theMM we have used amanual tracking plugin (MTrackJ) from Image J to track labeled red blood cells (RBCs) flowing around the boundary of the RBCs core. For the AM we have used a MatLab scripts to measure automatically the CFL trajectories. The preliminary numerical results suggest that the CFL trajectories follow a polynomial function for both methods.